12. William Russell: Polymath, Wordsmith, Classicist and Humourist. Issue 4 (September 2014) - Balls, Michael
Reading the The Principles of Humane Experimental Technique is a very special privilege, not only because of the importance of the messages it conveys, but because of the unique character and qualities of its principal author